Analisis Perhitungan Bagi Hasil Mudharabah Tabungan Pada (Studi Kasus) PT. Bank Pembiayaan Rakyat Syariah (BPRS)Harta Insan Karimah (HIK) Makassar - Muhadjir Suni (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2018)
This research is a qualitative descriptive study. by collecting descriptive data as outlined in the form of reports and descriptions. Data is obtained by approaching or documenting archives, documents, records or everything needed for this research. Then the data will be analyzed with qualitative analysis. The data that has been obtained will be validated by using the triangulation method, which is checking data from various sources in various ways, and at various times. There are two triangulation techniques namely source triangulation and technical triangulation. The results of the research conducted at BPRS HIK Makassar showed the mechanism for calculating the profit sharing system used using system revenue sharing with a ratio of 70:30. The revenue sharing system applies to the bank income that will be distributed calculated based on gross income. In BPRS HIK Makassar the Revenue sharing system mechanism is used by way of sharing the benefits of fund management carried out by the Bank before deducting operational costs or profit sharing calculated from gross profit / total income and using mudharabah mutlaqah and mudharabah muqayyadah contracts. So the revenue sharing system at BPRS HIK Makassar is in accordance with the National Shari'ah Council fatwa No: 02/DSNMUI/IV/2000 regarding the general provisions of savings based on Mudharabah.